Dynamic response characteristics of the Sapphire building in Istanbul estimated from earthquake and wind data - Savaş, Hakan Doğukan. (Thesis (M.S.)-Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2019., 2019)
The number of tall buildings has been increasing all around the world due to the current population growth and limited space in city centers. After major earthquakes, countries located in earthquake-prone areas face catastrophic conditions. In addition to building damages, deaths, and injuries, financial losses due to business interruption are also an important part of overall earthquake losses. Therefore, buildings home to organizations such as financial institutions, health care facilities, governmental buildings need to remain functional following an earthquake to constrain financial losses and secure public services. The condition of structures can be estimated by evaluating the change in the in-situ dynamic characteristics of the structures in real time day by day. In this study, the dynamic parameters of the Sapphire Building during strong wind and earthquake records are estimated in the time and frequency domain. Earthquake and wind events were selected from catalogs derived from Bogazici University Kandilli Observatory and Earthquake Research Institute Regional EarthquakeTsunami Monitoring Center and Bogazici University Kandilli Observatory and Earthquake Research Institute Meteorology Laboratory. In time domain analyses, correlations between peak accelerations, velocities, displacements; and magnitude and distance are estimated. The effects of faraway earthquakes on displacement time histories and damping are also investigated. Average drift ratios, computed from both wind and earthquake records, are compared with the limitations provided in the codes. In the frequency domain, natural frequencies, damping and mode shapes are identified by means of spectral analysis for wind and earthquake data. The result of wind and earthquake events on the Sapphire building are compared.
Keywords: Buildings -- Earthquake effects.; Wind-pressure -- Research -- Turkey.; Buildings -- Aerodynamics -- Research -- Turkey.; Structural dynamics -- Research -- Turkey.